Combination of polymyxin B and Aquilaria malaccensis extract enhanced the killing and inhibited the growth of Acinetobacter baumannii and Klebsiella pneumoniae - Nurul 'Izzati, Mohd Jihadi; Mahamad Maifiah, Mohd Hafidz; Nusaibah, Abdul Rahim; Abdullah Sani, Muhamad Shirwan; Hashim, Yumi Zuhanis Has-Yun; Khairunnisa, Mohd Kamal (Malaysian Society for Microbiology, 2022)
Aims: Polymyxins are an important last-line treatment for infections caused by multidrug-resistant Gram-negative bacteria. Nonetheless, the emergence of polymyxin resistance and the limiting of polymyxin monotherapy urgently demands its optimisation. Aquilaria malaccensis (Agarwood) has been widely used as traditional medicine. Many parts of the plant including leaves exhibit a considerable in vitro antibacterial activity against microbial pathogens. Exploiting A. malaccensis in combination with polymyxins provides a novel strategy in fighting antimicrobial resistance. The objective of this study was to evaluate the combination effects of A. malaccensis extract with polymyxins against Acinetobacter baumannii and Klebsiella pneumoniae. Methodology and results: In vitro time-kill studies and GC-MS analysis were performed to evaluate the bacterial killing of polymyxin B and extract combination and analyse chemical compounds of the extract, respectively. The combination of polymyxin B (1 mg/L) and A. malaccensis extract (32 mg/mL and 64 mg/mL) treatments exhibited enhanced bacterial killing compared to polymyxin B alone at 4 h and 24 h. Combination treatments also inhibited the bacterial growth of both A. baumannii and K. pneumoniae observed throughout the 24 h. More than sixty compounds including phytol, 9,12- octadecadienal, fatty acid, alkanes and terpenoids were putatively identified as the compounds that likely contributed to the antibacterial activity. Conclusion, significance and impact of study: This study was the first to report the potential application of A. malaccensis extract in combination with polymyxin B in treatment against A. baumannii and K. pneumoniae and can be further investigated and optimized for the treatment of bacterial infectious diseases.